Perceptions of bribery in Papua New Guinea's public sector: Agency and structural influences. (2nd June 2021) - Tiki, Samson; Luke, Belinda; Mack, Janet
Abstract: This study explores the perceptions of bribery among senior public servants within Papua New Guinea's (PNG's) government departments. Using structuration theory, consideration is given to individual, cultural and organisational factors influencing bribery, based on interviews with 11 senior public servants from three government departments. Findings reveal that most public servants acknowledged bribery exists in PNG's public sector. Perceptions of and perceived reasons for bribery typically reflected prioritisation of personal agency influenced by traditional and organisational (public sector) cultural norms, rather than responsibilities and accountabilities as agents operating within formal public sector structures.